What causes men's violence against women? - Harway, Michele; O'Neil, James M.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
This volume uses various theoretical perspectives to summarise what is known about the multiple causes of men's violence against women, and stresses the importance of identifying men's risk factors.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Abusive men; Men -- Socialization; Sex role; Women -- Abuse of; Wife abuse; Electronic books